2017
DOI: 10.1039/c6sc04206f
|View full text |Cite
|
Sign up to set email alerts
|

AIEgens for dark through-bond energy transfer: design, synthesis, theoretical study and application in ratiometric Hg2+ sensing

Abstract: A novel dark through-bond energy transfer (DTBET) strategy is proposed and applied as the design strategy to develop ratiometric Hg2+ sensors with high performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(85 citation statements)
references
References 56 publications
0
85
0
Order By: Relevance
“…Jiang et al [21] establishedalinear function between PL intensity and Hg 2 + concentration with only the PL intensity at 595 nm considered, which may be less accurate than using the PL intensity ratio (I 595 /I 480 )b ecauseo ft he different background signals generated at differentm easurements. Cheng et al [20] suggested that the relationships between I 595 /I 480 values and Hg 2 + concentrations should be used. The result of the present study was similar to that of Cheng et al, [20] in that the intensity ratio of I 595 /I 480 increased from 0.17 to 1038.6 when the amount of Hg 2 + increased from 1t o2equiv in the solution, which is an ennormous magnifying factor (> 6100-fold);h owever,c urve fitting was not performed in theirs tudy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jiang et al [21] establishedalinear function between PL intensity and Hg 2 + concentration with only the PL intensity at 595 nm considered, which may be less accurate than using the PL intensity ratio (I 595 /I 480 )b ecauseo ft he different background signals generated at differentm easurements. Cheng et al [20] suggested that the relationships between I 595 /I 480 values and Hg 2 + concentrations should be used. The result of the present study was similar to that of Cheng et al, [20] in that the intensity ratio of I 595 /I 480 increased from 0.17 to 1038.6 when the amount of Hg 2 + increased from 1t o2equiv in the solution, which is an ennormous magnifying factor (> 6100-fold);h owever,c urve fitting was not performed in theirs tudy.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al [20] suggested that the relationships between I 595 /I 480 values and Hg 2 + concentrations should be used. The result of the present study was similar to that of Cheng et al, [20] in that the intensity ratio of I 595 /I 480 increased from 0.17 to 1038.6 when the amount of Hg 2 + increased from 1t o2equiv in the solution, which is an ennormous magnifying factor (> 6100-fold);h owever,c urve fitting was not performed in theirs tudy. [20] In this study,t hen, the function for Hg 2 + concentration with AIEgen PL intensity was established for the firsttime by statistical analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Thus, there is no requirement for substantial spectral overlap between the donor emission and acceptora bsorbance, [2] leading to al arge pseudo-Stokes shifts (PSS) and emission shift, which is favorable to avoid self-quenching andf luorescence detectione rrors becauseo fe xcitation back-scattering effects. Althoughn umerousr atiometric fluorescence probes have been implemented with TBET mechanism, thesep robes are predominantly based on spirolactam ring-opening to sensing ions or molecules (Figure 1a), such as Hg 2 + ions, [4][5][6][7][8][9][10][11][12][13] Cu 2 + , [14][15][16] Pd 2 + , [17] Sn 2 + , [18] Ce 4 + , [19] À OCl, [20][21][22][23] picric acid [24] and so on. Althoughn umerousr atiometric fluorescence probes have been implemented with TBET mechanism, thesep robes are predominantly based on spirolactam ring-opening to sensing ions or molecules (Figure 1a), such as Hg 2 + ions, [4][5][6][7][8][9][10][11][12][13] Cu 2 + , [14][15][16] Pd 2 + , [17] Sn 2 + , [18] Ce 4 + , [19] À OCl, [20][21]…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Concurrently,n on-radiative decay is notorious in the area of luminescence studies,and scientists have devoted great efforts to suppress non-radiative decay for boosting luminescent efficacy.H owever,t he complete restriction of non-radiative decay cannot be achieved. [6] If so,h ow do we promote the probability of non-radiative decay of excited states? [6] If so,h ow do we promote the probability of non-radiative decay of excited states?…”
mentioning
confidence: 99%